Technical Note: Dosimetric effects of couch position variability on treatment plan quality with an MRI‐guided Co‐60 radiation therapy machine. Issue 8 (14th July 2016) - Chow, Phillip E.; Thomas, David H.; Agazaryan, Nzhde; Cao, Minsong; Low, Daniel A.; Yang, Yingli; Steinberg, Michael L.; Lee, Percy; Lamb, James M.
Abstract : Purpose: Magnetic resonance imaging (MRI) guidance in radiation therapy brings real‐time imaging and adaptive planning into the treatment vault where it can account for interfraction and intrafraction movement of soft tissue. The only commercially available MRI‐guided radiation therapy device is a three‐head 60 Co and MRI system with an integrated treatment planning system (TPS). Couch attenuation of the beam of up to 20% is well modeled in the TPS. Variations in the patient's day‐to‐day position introduce discrepancies in the actual couch attenuation as modeled in the treatment plan. For this reason, the authors' institution avoids plans with beams that pass through or near the couch edges. This study investigates the effects of differential beam attenuation by the couch due to couch shifts in order to determine whether couch edge avoidance restrictions can be lifted. Couch shifts were simulated using a Monte Carlo treatment planning system and ion chamber measurements performed for validation. Methods: A total of 27 plans from 23 patients were investigated. Couch shifts of 1 and 2 cm were introduced in combinations of lateral and vertical directions to simulate patient position variations giving 16 shifted plans per reference plan. The 1 and 2 cm shifts were based on shifts recorded in 320 treatment fractions. Results: Following TG176 recommendations for measurement methods, couch attenuation measurements agreed with TPS modeled attenuation to within 2.1%. Planning target volume D 95 changed less than 1% for 1 and 2 cm couch shifts in only the x ‐direction and less than 3% for all directions. Conclusions: Dosimetry of all plans tested was robust to couch shifts up to ±2 cm. In general, couch shifts resulted in clinically insignificant dosimetric deviations. It is conceivable that in certain cases with large systematic couch shifts and plans that are particularly sensitive to shifts, dosimetric changes might rise to a clinically significant level.